Shnider and Levinson's anesthesia for obstetrics - Suresh, Maya. (Philadelphia : Wolters Kluwer Health/Lippincott Williams & Wilkins Health, 2013)
Now in a fully updated Fifth Edition, Shnider and Levinson's Anesthesia for Obstetrics, continues to provide the comprehensive coverage that has made it the leading reference in the field. The rising number of Cesarean births and the more advanced age of first-time mothers in the United States have brought with them an increased risk for complications, making the role of the obstetric anesthesiologist increasingly important. Inside you'll explore ... Maternal and Fetal Physiology builds your understanding of placental transfer of drugs. Fetal Assessment covers the basics of antenatal assessment and intrapartum monitoring. Anesthesia and Analgesia addresses the anesthetic considerations of vaginal and Cesarean delivery. Neonatal Well-Being--including neonatal resuscitation and neonatal injury. Management of Obstetric Complications helps minimize the risks posed by abnormal positioning, intrapartum fever, and antepartum and postpartum hemorrhage. Management of Anesthetic Complications addresses the special problems related to obstetric anesthesia, including embolic events and intubation problems. Management of the Parturient with Coexisting Disorders prepares you for the special challenges faced when treating mothers with hypertensive, respiratory, endocrine, neurologic, or other disorders. Difficult and Failed Intubation: Strategies, Prevention, and Management of Airway-Related Catastrophes addresses the airway related maternal mortality, predictors of difficult airway and strategies to manage the unanticipated difficult airway as well as the critical airway with increasing hyoxemia. NEW to the Fifth Edition ... New editorial teamew full-color format. New sections on Assessment of the Fetus; Anesthesia for Cesarean Delivery; Neonatal Well-Being: Old and New Concepts; Ethical, Medical, and Social Challenges and Issues; Maternal Safety, Difficult and Failed Intubation, Morbidity, and Mortality; and Anesthetic Considerations for Reproductive, In-Utero, and Non-Obstetric Procedures"--Provided by publisher.
section I. Physiology and pharmacology -- section II. ASsessment of the fetus -- section III. Anagesia and anesthesia for labor and vaginal delivery -- section IV. Anestesia for cesarean delivery: managemnt of postoperative and postartum issues -- section V. Neonatal well-being: old and new concepts -- section VI. Anesthetic considerations and management of obstetric complications -- section VII. Risks, strategies and management of anesthetic complications -- section VIII. Anesthetic management of the parturient with coexisting disorders -- section IX. Ethical, medical, and social challenges and issues -- section X. Maternal safety, morbidity, and mortality -- section XI. Anesthetic considerations for reproductive, in-utero and non-obstetric procedures.
Includes bibliographical references and index.
Description based on print version record.
Electronic reproduction. Palo Alto, Calif. : ebrary, 2014. Available via World Wide Web. Access may be limited to ebrary affiliated libraries.
Keywords: Anesthesia in obstetrics; Anesthesia; Obstetrics; Electronic books